Streptomyces sp. CLV45 from Fabaceae rhizosphere benefits growth of soybean plants - Horstmann, Juliana Lopes (Braz J Microbiol, 2020)
Plant growth-promoting bacteria such as Streptomyces are an attractive alternative for increasing the sustainability of agricultural systems. In this study, Streptomyces isolates obtained from rhizosphere soil of plants in the family Fabaceae were characterized for their plant growth-promoting traits, including the production of siderophores, 1-aminocyclopropane-1-carboxylate (ACC) deaminase, indole-3-acetic acid (IAA), and phenazines. Soybean seeds were bacterized with selected isolates to test growth promotion. All isolates produced IAA, and the isolate CLV45 was the most efficient, reaching 398.53 mg of IAA per gram of cells. CLV41, CLV45, and CLV46 showed high activity for ACC deaminase whereas CLV42, CLV44, and CLV46 were efficient in siderophore production. Pyocyanin was detected in all isolates; CLV41, CLV43, and CLV45 produced phenazine-carboxylic acid as well. Selected for IAA and ACC deaminase production combined with production of siderophores and phenazines, CLV42, CLV44, and CLV45 were tested for their growth promotion potential. Seed bacterization with CLV45 resulted in plants with increased shoot growth (36.63%) and dry mass (17.97%) compared to control plants. Results suggest that moderate or high levels of auxin and ACC deaminase production by the isolate CLV45 positively affected the growth of soybean plants, making it a strong candidate for further studies on biofertilizer formulation.